2021
DOI: 10.1037/pas0000981
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese version of the Multidimensional Assessment of Parenting Scale.

Abstract: Parenting practices have been linked to a wide range of issues related to children's psychological adjustment; however, more research is warranted to further understand not only cultural variations of parenting norms, but also how such variations might differentially influence child outcomes. The current study examined the psychometric properties of a Chinese translation of the Multidimensional Assessment of Parenting Scale (MAPS) in order to: 1) assess both positive and negative dimensions of parenting in Chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Another bilingual PhD-level professor of child development and another doctoral candidate in developmental psychology, both of whom were not involved in the initial translation of the Mandarin MAPS, completed the back-translation process from Mandarin Chinese to English independently. The back-translators discussed discrepancies and then created a final back-translation (for further details, see Ahemaitijiang et al, 2021). English-speaking parents completed the MAPS via Amazon Mechanical Turk (https://www.mturk.com) as part of a larger study on parenting within the United States, whereas Mandarin-speaking parents completed the MAPS via Qualtrics surveys online as part of a larger study on mindfulness and parenting in Mainland China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another bilingual PhD-level professor of child development and another doctoral candidate in developmental psychology, both of whom were not involved in the initial translation of the Mandarin MAPS, completed the back-translation process from Mandarin Chinese to English independently. The back-translators discussed discrepancies and then created a final back-translation (for further details, see Ahemaitijiang et al, 2021). English-speaking parents completed the MAPS via Amazon Mechanical Turk (https://www.mturk.com) as part of a larger study on parenting within the United States, whereas Mandarin-speaking parents completed the MAPS via Qualtrics surveys online as part of a larger study on mindfulness and parenting in Mainland China.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were age-matched subsamples as a part of two separate research protocols in China (Ahemaitijiang et al, 2021) and the United States (Parent & Forehand, 2017). All procedures were reviewed and approved by the institutional review board of Beijing Normal University and University of Vermont.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPS is a 34-item questionnaire assessing parenting practices with strong psychometric properties reported in both the original and Chinese versions ( Parent and Forehand, 2017 ; Ahemaitijiang et al, 2021 ). Given the relevancy to the CAPS and applicability to the developmental stage of the sample, three subscales, namely, “Proactive Parenting,” “Positive Reinforcement” and “Supportiveness,” were chosen to be outcome measures of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis by Gershoff and Grogan-Kaylor indicated that 69.4% of harsh parenting studies were from the United States [ 21 ], with the remaining small number of studies from Western Europe, and that there is a paucity of relevant studies based on Eastern cultural backgrounds. One example is that of Ahemaitijiang et al [ 22 ] who validated both positive and negative dimensions of parenting to measure parenting styles in the Chinese cultural context. Therefore, the generalizability of the link between harsh parenting and suicidal ideation in Eastern cultural contexts needs to be further tested.…”
Section: Introductionmentioning
confidence: 99%